Epidemiological characteristics of renal stone patients age (21-60) and barriers in their dietary modification in Saurashtra Region - Patel, Arpan Chandubhai; Mehta, Nishank Harris (International Journal of Research in Medical Sciences, 2017)
Background: Dietary factors remain an entity attributed to a kidney stone and thus renal stone becomes more of a ’lifestyle’ disease relying more on prevention for its amelioration than advanced and specific treatment modalities. Although there are various studies conducted in past to show importance of dietary modification in patient with kidney stone , no single study was conducted to identify perceived barriers in dietary modification by patient. Methods: Through this population based cross-sectional study, a total of 50 patients with a radiologically diagnosed ‘case’ of renal stone were enrolled in the study and interviewed through proforma approved by institutional ethical committee to study patients characteristics and perceived barriers in dietary modification. Data were analyzed with help of Epi Info™ 7 (CDC Atlanta). Results: Kidney stone prevalence is higher in men (66%) in compare to females and common with age group 31-40 years. Hindu caste (82%), low socioeconomic status (76%), and education less than 8th (42%) and not aware of need (62%) were common characteristics among them. Not clearly informed about benefits of Diet modification (54%) and Don’t Remember (42%) constituted common barriers. Conclusions: Along with educating them regarding kidney stone disease it is important to identify all barriers at individualize level because motivating patients with kidney stones to maintain behavior for recommended diet, first requires an understanding of the factors influencing this behavior and approach should be tailored for individual patient.